The State of Solid Waste Management Challenges as Exacerbated by COVID-19 Pandemic Related Littering in Addis Ababa City Administration - Metaferia, Markos Sintayehu (Journal of Urban Development Studies, 2022)
This study is concerned in the examination of state of solid waste management and the challenges related to exacerbation of COVID-19 attached littering in Addis Ababa city administration. The study explored the challenges and effects of COVID -19 in one of the areas where the environmental impacts of the pandemic are most prominent, the solid waste management sector. A total of 455 survey questionnaires were distributed and collected with a response rate of almost 100% from under 7 sub-cities considering some specially identified problematic areas which are known to have recurrent unattended littering problems due to human& economic activities as pathway. A mixed cross sectional survey research approach was used along with a structured questionnaires & sideline interviews. As one prime focus/objective of the study to assess and evaluate the magnitude of the problem of the challenges resulted due to COVID -19 on the SWM sector the Likert scale type survey questionnaire were analyzed quantitatively by using mean score and percentages. The challenges and magnitude of the problems resulted due to COVID-19 pandemic on the SWM and on the overall aspects of the sector is a moderately significant challenge as having or acquiring an average mean score value of 3.42 or (68.46% ).Considering the full extent of the problem in terms of the computed percentage amount, this may probably sound in a justifiable sense that, the magnitude of the problem of the challenge of COVID-19 on the SWM sector is by about 68.46% during the tough times of the COVID-19 pandemic.